The influence of the metal foam layer shape on the thermal charging response time of a latent heat thermal energy storage system - Fteiti, Mehdi A.; Ghalambaz, Mohammad; Younis, Obai; Sheremet, Mikhail A.; Ismael, Muneer (Journal of energy storage)
In the current study, the impact of various foam shapes and configurations was addressed for the first time on the thermal energy storage rate. A partial layer of metal foam was used to improve the heat transfer rate in a channel-shaped latent heat thermal energy storage unit for solar thermal energy storage. The channel was heated at the right vertical wall while half of the channel was filled with a layer of metal foam. The enthalpy porosity model was utilized for simulating the melting heat transfer in the channel. The finite element method was employed to solve the governing equations. Several design configurations for the placement of the metal foam layer were examined. The findings showed that placing the metal foam layer in an L shape form along the left and bottom walls could yield maximum thermal energy storage power (0.57 kW). Diagonal placement of the porous layer along the right and bottom walls gives the lowest thermal energy storage power (0.23 kW). Therefore, changing the shape of the metal foam layer could alter the storage power by about 60 % for a fixed amount of metal foam. Therefore, the shape of the metal foam layer is an important design parameter that should be selected carefully.